Direct investment as seen by German Industry - Wolfgang Pohle (Intereconomics, 1971)
The pros and cons of direct investment are attracting more and more attention in public discussion. In the following article, Dr Pohle, who was not only a highly successful businessman but also an influential and much respected Member of Federal Parliament, examined the possible positive and negative repercussions of direct investment from the point of view of German industry.
Keywords: 330; Development policy